Gadget Use on Students' Social And Religius Interactions in SDN 82, Bengkulu City - Della Fusvita; Ananda Talia Salsa Billa; Kurniawan; Adam Nasution; Hendro Ade Saputra (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to describe the impact of gadget use on social interactions among fifth-grade students at SDN 82, Bengkulu City, based on field observations. The focus of this study is on the impact. The use of gadgets and the role of teachers in anticipating the impact of gadget use on students' social interactions at SDN 82 Bengkulu City. The research method used is a descriptive method with a qualitative research approach. Data were collected through interviews, observation and documentation. The analysis techniques used in this study are data collection, data reduction, data presentation, and drawing conclusions or verification. The triangulation used is source triangulation. The results of the study show that there are positive and negative impacts of gadget use in social interactions at SDN 82 Bengkulu City. The positive impacts are 1) it can help students establish communication with parents and distant friends, 2) making it easier for students to obtain school information, 3) polite behavior, 4) empathy, 5) discipline, and 6) responsibility. While the negative impacts are 1) students become insensitive to what is conveyed by the teacher, 2) gadgets as an obstacle to students' social interactions, 3) apathy, and 4) bullying . Meanwhile, the role of teachers in anticipating the impact of gadget use in students' social interactions is 1) Teacher as a guide, 2) counselor, 3) role model, 4) visionary person, and 5) advisor. Based on the results of the study above, it can be concluded that there is an impact of gadget use on the social interactions of students in class V SDN 82 Bengkulu City, both positive and negative impacts. Therefore, the role of teachers is very necessary in anticipating the impact of gadget use in students' social interactions in class V SDN 82 Bengkulu City.